Minimization of natural fires - Lyushvin P.B. (IJRDO-Journal of Applied Science, 2020)
Annually in the mid-latitudes with the onset of heat, and in the tropics - dry season, there are massive fires. The combination of focal maps of fires with geological information in a number of regions of Russia (Moscow, Urals and Siberia), as well as in the Far East, the Mediterranean, India, North and Latin America, Tasmania) indicates the geological linking of a significant part of the fires to positive anomalies of the magnetic field and mass degassing of methane, as well as the basic connection with tides, solar and geomagnetic activity. It is assumed that in the zone of rifts of the earth’s crust there occur: activation of deep-seated channels of increased heat and mass transfer (emanation of fluids), abrupt changes in the amplitude-frequency characteristics of electromagnetic fields, ionization of air, formation of "static" minima of atmospheric humidity, reduction of precipitation, occurrence of atmospheric lineaments. Analysis of the above suggests a number of schemes for forecasting and preventing dangerous phenomena of different lead times. Recommendations are given to minimize damage from natural fires. An international action program (roadmap) is proposed, including scientific and applied research, the development of an ultra-short-term monitoring and warning system and an emergency service with technical means for eliminating foci of fires.